2012
DOI: 10.1515/2161-962x.1011
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for Bias due to Misclassification when Error-prone Continuous Exposures Are Misclassified

Abstract: To investigate the association between a continuous exposure and an outcome it is common to categorize the exposure and estimate the relative associations between categories. Error in measurement of the continuous exposure results in misclassification when the exposure is categorized. In this paper we investigate methods for correcting for this misclassification. We consider applications of methods for continuous exposures and for fundamentally categorical exposures. A particular challenge is that even nondiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Misclassification might happen due to the measurement error in the LOT-R, which can cause potential bias in either direction. 47 Third, patients with lower dispositional optimism and poor HRQL might be more likely to decline to participate in the study and not answer the follow-up questionnaires, which could make the observed associations underestimated. Last but not least, prediction does not equal causation.…”
Section: Discussionmentioning
confidence: 99%
“…Misclassification might happen due to the measurement error in the LOT-R, which can cause potential bias in either direction. 47 Third, patients with lower dispositional optimism and poor HRQL might be more likely to decline to participate in the study and not answer the follow-up questionnaires, which could make the observed associations underestimated. Last but not least, prediction does not equal causation.…”
Section: Discussionmentioning
confidence: 99%
“…Classical error in a multivariate exposure setting can result in bias in any direction even in a linear regression model [4]. Where there are non-linear terms, for example, a quadratic term, in the exposureoutcome model, classical measurement error has the effect of making the association appear more linear [32]. Other types of error, such as systematic error, which depends on the true exposure; heteroscedastic error; and differential error, which depends on the outcome, may in general result in biases of any form, for example, bias either away from or towards the null [4,33].…”
Section: Effects Of Measurement Errormentioning
confidence: 99%
“…Recently Keogh et al 128 investigated several methods of adjusting for misclassification due to dichotomizing a continuous error-prone predictor. In contrast to previous work, a measured continuous exposure was specified to follow a linear measurement error model, thereby allowing for systematic error.…”
mentioning
confidence: 99%